The Impossibility of a Theoretical Science of Economic Dynamics - Northrop, F. S. C. (Quarterly Journal of Economics, 1941)
No scientific theory of economic dynamics exists, 1. — The basic concepts and postulates of contemporary economic theory, 3. — The method of constructing and verifying traditional economic theory, 6. — Theoretical dynamics of Newtonian mechanics, 8. — Economics compared with physics, 10. — Bearing of this upon the possibility of a theoretical economic dynamics, 12. — The precise capacity of contemporary economic theory, 13. — Diagrammatical summary, 16.